ANALISIS DAMPAK PENGKAJIAN TEKNOLOGI PERTANIAN UNGGULAN SPESIFIK LOKASI TERHADAP PRODUKTIVITAS KASUS: BPTP NUSA TENGGARA TIMUR - NUR SUHAETI, RITA; BASUNO, EDI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Impact Analysis of Improved and Location Specific Agricultural Technologies on Productivity, AIAT East Nusa Tenggara Case. By selecting six topics of improved research and assessments (R&A), impact analysis on productivity had been carried out in 2002 fiscal year. However, only four out of six topics were analyzed, because the other two were still in adaptive level. Application of introduced technologies, in fact, resulted in some additional yield. The highest production and productivity were experienced by R&A of Backyard Farming System, i.e. 569.63 percent, then followed by Milk Fish Culture, Bisma Corn Based Agribusiness, Beef Cattle Based Agribusiness 482.10 percent, 284.76 percent and 45.0 percent, respectively. Corn Agribusiness gave the largest impact area of 1,365 ha, while its impact on production was also excellent, by adding production of 2,319,308.33 kg/planting season. Milkfish culture, on the other hand gave the highest income/ha per production cycle. Based on relatively high MBCRs, all analyzed topics were feasible to be developed in the future. Milkfish culture on brackish water was the most profitable business, reflected by the highest MBCR of 14,08. MBCR figures for Backyard Farming, Beef Cattle Agribusiness and Bisma Corn Agribusiness were 1.38, 6.24 and 8.61, respectively. Cost and price ratio of each topics were 0.47; 0.21; 0.22 and 0.33 for Backyard Farming System, Bisma Corn Agribusiness, Milk Fish Culture and Beef Cattle Agribusiness, respectively. The smallest adoption cost per Kg product was indicated by Backyard Farming System (Rp 935.85), followed by Bisma Corn Agribusiness (Rp 1,028.30) and Milk Fish Culture (Rp 2181.32), while the highest was for Beef Cattle Agribusiness (Rp 9,770.03).
Keywords: Impact study, Research and assessment, Location specific, East Nusa Tenggara